Diagnosa Gangguan Obsessive Compulsive Disorder dengan Kombinasi Metode Ripple Down Rules dan Certainty Factor - Silaban, Lenni Wati; Ramadani, Sindi Fitri; Sembiring, David JM; PA, Sinek Mehuli Br (Journal Global Technology Computer, 2025)
Obsessive Compulsive Disorder (OCD) is a mental health disorder that is gaining increasing attention in the medical world and society. In Indonesia, public awareness and understanding of OCD are still low. Many OCD sufferers are unaware that they have this disorder. The main problem with OCD lies in its complex nature and difficulty in early recognition. Many OCD sufferers are unaware that their behavior is clinically abnormal because the symptoms are often considered common habits. The impact of these problems can have quite serious ongoing consequences. Individuals with OCD experience a decreased quality of life due to anxiety and compulsive behaviors that consume time and energy. In this study, the solution offered is to develop an expert system based on Ripple Down Rules (RDR) and Certainty Factor (CF). The purpose of this study is to increase public awareness and understanding of OCD, develop a system capable of making a quick and accurate initial diagnosis, facilitate the identification of OCD types, especially the Checking type, and provide support for medical personnel and psychological counselors in the initial diagnosis process. In the diagnostic calculation, the results show that Checking disorder has a percentage of 97.35%.